WHEN BUMN SUBSIDIARIES BECOMES THE "ALTER EGO" OF THE STATE: ANALYSIS OF THE SUPREME COURT CIRCULAR LETTER NUMBER 10 OF 2020 (SEMA 10/2020) REGARDING THE CORRELATION BETWEEN "BUMN SUBSIDIARIES LOSS” AND “STATE LOSS” - D. Hutagaol, Henry (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
There is a clear distinction between the legal character of the State and that of the Company. While the state’s purpose is to serve the public, a company is ultimately formed for the purpose of gaining Profit. The theories of legal entities and Corporate Law argue that the formation of a legal entity, especially a Limited Liability Company (PT) is intended to separate assets and liabilities between a Legal Entity (Company) and its Shareholders. If the shareholders (State) do not intend to segregate both assets and liabilities, the state does not need to establish a Company from the beginning. Since the issuance of Law 17/2003 on State Finances, the legal extent pertaining to state assets has become increasingly blurred, because Law 17/2003 states that "State assets that have been segregated remain within the scope of state finances". This regulation complicates the legal status of BUMN[1] assets. Furthermore, the wealth status of BUMN Subsidiaries (AP BUMN)[2] experiences the same issue. Hence, one question arises: are Segregated Assets (Paid up Capital Injection by BUMN) still considered assets of the state or are they fully owned by the Company? The Supreme Court (Mahkamah Agung/MA), as of 18 December 2020, issued SEMA[3] 10/2020. Therein, point 4 of the Summary of the Criminal Chamber outlines that "Losses arising from BUMN/BUMD subsidiaries whose capital is not sourced from the APBN/APBD or through capital injection by the BUMN/BUMD and does not receive/utilize state facilities, will not constitute a part of the State’s financial loss”. This adds to the uncertainty because, from a legal perspective, the Shareholder of an AP BUMN is the BUMN itself (and not the State), thus creating a legal correlation that extends to considering AP BUMN Loss as State Loss, and creates a legal uncertainty. [1] BUMN (Badan Usaha Milik Negara) is State Owned Enterprises (SOE)[2] AP BUMN (Anak Perusahaan BUMN) is the SOE Subsidiary Company[3] SEMA (Surat Edaran Mahkamah Agung) is a Circular Letter (Administrative Policy) from Supreme Court to all courts in Indonesia.